2019
DOI: 10.1155/2019/7641767
|View full text |Cite
|
Sign up to set email alerts
|

Generation of iPSCs by Nonintegrative RNA-Based Reprogramming Techniques: Benefits of Self-Replicating RNA versus Synthetic mRNA

Abstract: The reprogramming of somatic cells into induced pluripotent stem cells (iPSCs) is gaining in importance in the fields of regenerative medicine, tissue engineering, and disease modeling. Patient-specific iPSCs have as an unlimited cell source a tremendous potential for generating various types of autologous cells. For the future clinical applicability of these iPSC-derived cells, the generation of iPSCs via nongenome integrating methods and the efficient reprogramming of patients’ somatic cells are required. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 38 publications
0
33
0
Order By: Relevance
“…Hence, there is an urgent need for further optimization. Since mRNAs are degraded over time, multiple transfection steps might increase the reprogramming efficiency, a strategy that is already applied for the generation of iPSCs from adult cells [74,80]. Moreover, proportions of GATA4, MEF2C, and TBX5 protein expression has been described to play a crucial role for the quality of cardiac reprogramming [81], thus, different ratios of transfected mRNA could positively influence the outcome of reprogrammed adMSC.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, there is an urgent need for further optimization. Since mRNAs are degraded over time, multiple transfection steps might increase the reprogramming efficiency, a strategy that is already applied for the generation of iPSCs from adult cells [74,80]. Moreover, proportions of GATA4, MEF2C, and TBX5 protein expression has been described to play a crucial role for the quality of cardiac reprogramming [81], thus, different ratios of transfected mRNA could positively influence the outcome of reprogrammed adMSC.…”
Section: Discussionmentioning
confidence: 99%
“…To circumvent innate immune activation, lessons could be learned from viruses, as they have developed effective strategies to bypass innate immunity (Schulz and Mossman 2016). Co-expression of virally delivered IFN modulating proteins could be an effective solution for mRNA-based reprogramming approaches (Yoshioka and Dowdy 2017;Steinle 2019). To reduce PRR stimulation and consequent reduction of self-amplifying mRNA translation, Beissert et al have demonstrated that antigen expression from self-amplifying mRNA can be significantly improved in vitro and in vivo by co-transferring mRNAs encoding IFN and PKR inhibitory proteins, such as viral protein B18R, a decoy receptor of vaccinia virus, which binds type I IFNs (Beissert 2017).…”
Section: Self-adjuvanting Effect Of the Self-amplifying Mrnamentioning
confidence: 99%
“…Utilizing mRNA to express reprogramming factors has high efficiency, which can be even further improved by adding Lin28 to the Yamanaka reprogramming factors [ 33 ]. Culturing at 5% O 2 with addition of valproic acid in the medium also enhances efficiency [ 34 ].…”
Section: Reprogramming Of Somatic Cells Into Ipscsmentioning
confidence: 99%